Floral symbolism in Ukrainian painting of the second half of the 20 th century - Butovska, O. (Art and Design, 2025)
The relevance of the study is determined by the need for a comprehensive study of floral symbolism as an important means of preserving and the transmission of national identity in Ukrainian painting during the period of ideological restrictions (1940s-1980s), which is of particular importance for understanding the mechanisms of cultural resistance and the formation of national consciousness. The aim of the study was to conduct a comprehensive analysis of the development of floral symbolism in Ukrainian painting in the second half of the 20 th century and to determine its role in the formation of national artistic identity. A set of art history methods was applied: iconographic analysis of symbolic meanings, stylistic analysis of artistic features, and a semiotic approach to reveal the system of symbols. The work of leading Ukrainian artists (M. Glushchenko, V. Kostetsky, T. Golembiievska, I. Krasny, O. Shovkunenko, T. Yablonska, E. Volobuev) in the period from 1940 to 1980 was analysed. The evolution of floral symbolism is traced from the symbols of hope in the 1940s through the search for national identity during the “thaw” period to the philosophical understanding of being. The research has clarified the symbolic meaning of key floral motifs, for example, the peony is associated with rebirth, the cornflower with love for the native land, the mallow expresses the idea of family well-being, and the combination of the daffodil and the ear of corn embodies the cyclical nature of nature. The use of floral images as a means of indirectly expressing patriotic feelings in conditions of ideological restrictions has been proven. It has been established that the multi-layered semiotic system created by artists functioned at the level of individual expression and collective memory, which ensured the transmission of national values in changing historical conditions. The results of the study can be used in teaching Ukrainian art history, art history, cultural studies, curatorial activities, and the creation of museum exhibitions